Reuse of Wastewater: Concerns about the Effects of Mixtures of Chemical Substances on Human Health - José Cabêda; Carina Ladeira (Proceedings, 2024)
Due to global warming, new practices should be adopted in the use of wastewater in the agricultural, industrial, and urban sectors [...]